Juridical Study of Ownership of Ownership of Flats by Foreign Citizens Based on Government Regulation Number 18 of 2021 concerning Land Rights Management Rights for Flats Units and Land Registration - Sari, Eriza Yulistiana; Yunita Reykasari (Indonesian Journal Publisher, 2024)
This study aims to determine and understand the Ownership of Usage Rights of Apartment Units by Foreign Citizens Based on the Theory of Benefit. The research methods used include a statute approach and a conceptual approach, a type of normative legal research, with data collection methods through library surveys and qualitative legal analysis. The results of the study indicate that Government Regulation Number 18 of 2021 provides a legal basis for foreign citizens to have usage rights over apartment units in Indonesia but does not provide full ownership rights, this regulation provides legal certainty and clear procedures, which are expected to be further elaborated in the Ministerial Regulation. The Indonesian government needs to consider allowing foreign citizens to have ownership rights over apartment units by considering the various benefits that can be obtained. This step can increase foreign investment, encourage economic growth, improve property quality, stabilize the property market, increase state revenues, and support infrastructure development. With proper regulation and strict supervision, this policy can provide significant benefits to the Indonesian economy and society as a whole.